2018
DOI: 10.1080/13102818.2018.1459208
|View full text |Cite
|
Sign up to set email alerts
|

Conversion from natural wetlands to forestland and farmland alters the composition of soil fungal communities in Sanjiang Plain, Northeast China

Abstract: To understand the effect of human activities on fungal communities in wetland, forestland and farmland soils, in this study, we investigated the relationship between the composition of soil fungal communities and their perturbations in wetland in northeast China. The results showed that a total of 132 OTUs were identified from all three site types combined, while 72 were exclusively shared between farmland and pristine wetland, 60 between forestland and pristine wetland, and 305 between farmland and forestland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
(42 reference statements)
0
2
2
Order By: Relevance
“…Qin discovered that the diversity of soil fungi was higher in other land use types than in farmland soils. In another study conducted by Zhang et al (2018) on the Sanjiang Plain Wetland, they found that soil fungal diversity in natural wetlands was significantly lower than that in croplands following the transition from natural wetlands to croplands, which is different from our findings. This may be due to the differences in soil physicochemical properties caused by the different geographical locations of our research and Zhang et al (2018) .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Qin discovered that the diversity of soil fungi was higher in other land use types than in farmland soils. In another study conducted by Zhang et al (2018) on the Sanjiang Plain Wetland, they found that soil fungal diversity in natural wetlands was significantly lower than that in croplands following the transition from natural wetlands to croplands, which is different from our findings. This may be due to the differences in soil physicochemical properties caused by the different geographical locations of our research and Zhang et al (2018) .…”
Section: Discussioncontrasting
confidence: 99%
“…In another study conducted by Zhang et al (2018) on the Sanjiang Plain Wetland, they found that soil fungal diversity in natural wetlands was significantly lower than that in croplands following the transition from natural wetlands to croplands, which is different from our findings. This may be due to the differences in soil physicochemical properties caused by the different geographical locations of our research and Zhang et al (2018) . Through the Pearson analyses, we found that soil fungal diversity was negatively correlated with pH, possibly due to a decrease in soil pH associated with the extension of the time of wetland restoration, leading to slightly acidic ( Table 1 , p < 0.05).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Wei et al (2019) showed that the response of soil microbial communities to human activities is varied. H. Zhang et al (2018) found that wetland conversion resulted in changes in soil fungal community pattern. However, the comparative characteristics of soil microbial community in different degraded types of wetlands are not clear.…”
Section: Introductionmentioning
confidence: 99%